The Extreme Right as a Philosophical and Psychoanalytic Problem: About “Liber-Fascism” and Its Modalities of Jouissance; [la Extrema Derecha Como Problema Psicoanalítico: Acerca del “Liberfascismo” y Sus Modalidades de Goce] - Letelier-Soto, A (Universidad De Valparaíso, Chile, 2023)
The aim of this article is to problematize, from a sociopolitical and psychoanalytic point of view, the current rise of the new rights, especially in Latin America. Although this extremist renaissance is loosely and indicatively referred to as fascism, we believe that, after careful analysis, today’s far-rights are not simple repetitions of the fascisms of the s. XX. It is about an unprecedented governmentality and ideology that, on the one hand, is not reduced to neoliberalism and, on the other hand, surpasses the European-Anglo-Saxon alt-right and contemporary libertarianism. We give it the particular name of liber-fascism, to the extent that it brings a new mode of political subjectivation: the defender of himself. We divide the text into two sections. In the first, we discuss the sociopolitical particularities of liber-fascism: the emergence of a social ontology of the defender of himself that conceives of the capitalist market as an instance to be defended using false news, conspiracy theories and, of course, organized violence. In the second, we clarify the functioning of the liber-fascist unconscious by analyzing the peculiarity of its fantasy: it is an ideology that, in its relationship with others, uses violence no longer as a simple means, but as a vehicle for jouissance. © 2023 Instituto de Filosofía, Universidad de Valparaíso.